Emergency contraception - Gemzell-Danielsson, Kristina; Rabe, Thomas; Cheng, Linan (Gynecological endocrinology, 2013)
There have been numerous attempts to control fertility after unprotected sexual intercourse (UPSI). From very bizarre methods like the vaginal application of Coca Cola to the more serious attempts using calcium antagonists influencing fertility parameters in sperm to hormonal methods or intrauterine devices. So far, hormonal methods preventing or delaying ovulation have proved to be the most popular starting with the combination of ethinyl estradiol and levonorgestrel (LNG), known as the Yuzpe regimen. The first dose had to be taken within 72 hours of UPSI, a second one 12 hours later. Later on, LNG alone, at first in a regimen similar to the Yuzpe method (2 × 0.75 mg 12 hours apart) showed to be more successful, eventually resulting in the development of a 1.5 mg LNG pill that combined good efficacy with a high ease of use. Several efficacious and easy to use methods for emergency contraception (EC) are available on the market today with the most widely spread being LNG in a single dose of 1.5 mg (given as one tablet of 1.5 mg or 2 tablets of 0.75 mg each) for administration up to 3 days (according to WHO up to 5 days) after UPSI. Its limitations are the non-optimal efficacy which is decreasing the later the drug is taken and the fact that it is only approved for up to 72 hours after UPSI. This regimen has no effect on the endometrium, corpus luteum function and implantation, is not abortive and don't harm the fetus if accidentally taken in early pregnancy. It has no impact on the rate of ectopic pregnancies. It has become the standard method used up to this day in most countries. Since the mid 1970s copper IUDs have been used for EC, which show a high efficacy. Their disadvantages lie in the fact that EC is considered an off label use for most IUDs (not for the GynFix copper IUD in the European Union) and that they might not be acceptable for every patient. Furthermore IUD-insertion is an invasive procedure and it is required trained providers and sterilized facilities. Mifepristone in the dosages of 10 or 25 mg is used with good results as an emergency contraceptive in China for up to 120 hours after UPSI, but has never received any significant consideration in Western countries. While high doses of mifepristone has an effect on endometrial receptivity and will inhibit ovulation if given in the follicular phase and prevent implantation if given in the early luteal phase, low doses such as 10 mg has no impact on the endometrium. Mifepristone does not increase the rate of ectopic pregnancies. The most recent development is the approval of the selective progesterone receptor modulator ulipristal acetate (UPA) in the dosage of 30 mg for EC up to 5 days after UPSI, combining the safe and easy application of the single dose LNG pill with an even higher efficacy. It has shown to be more efficacious than LNG and can be used for up to 120 hours after UPSI; the difference in efficacy is highest for 0-24 hours, followed by 0-72 hours following UPSI. No VTE has been reported following UPA-administration or any progesterone receptor modulator. No effect on endometrium, corpus luteum function and implantation has been observed with doses used for EC. Independent of the substance it should be noted that, if there is a choice, the intake of an oral emergency contraceptive pill should happen as soon as possible after the risk situation. A preexsisting pregnancy must be excluded. Possible contraindications and drug interactions must be considered according to the individual special product informations.
Gesehen am 03.02.2020